2021
DOI: 10.1155/2021/5541995
|View full text |Cite
|
Sign up to set email alerts
|

Yoga as an Adjunct for Management of Opioid Dependence Syndrome: A Nine-Month Follow-Up Case Report

Abstract: Opioid dependence syndrome (ODS) is a chronic relapsing remitting condition associated with significant impairment and mortality risk. Opioid substitution therapy is used worldwide, but long-term retention rates are low and there is risk of misuse and diversion. Yoga practice can improve quality of life, reduce chronic pain, and enhance endogenous opioids (beta-endorphins). We describe a case of ODS where yoga was added to the conventional management and who was followed up for 9 months. Assessments were done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…We have been offering tele-yoga services to healthy people for stress management and to patients suffering from mental health disorders for over a year now 49 . In a pilot feasibility study, we found tele-yoga to be feasible and acceptable in patients with substance use disorders including OUD patients 50 , 51 and have also observed an increase in plasma endorphin levels immediately after yoga practice in healthy participants 52 . Tele-medicine offered by the National Institute of Mental Health and Neurosciences (NIMHANS), Bengaluru has been found acceptable and feasible for psychiatric patients 53 .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have been offering tele-yoga services to healthy people for stress management and to patients suffering from mental health disorders for over a year now 49 . In a pilot feasibility study, we found tele-yoga to be feasible and acceptable in patients with substance use disorders including OUD patients 50 , 51 and have also observed an increase in plasma endorphin levels immediately after yoga practice in healthy participants 52 . Tele-medicine offered by the National Institute of Mental Health and Neurosciences (NIMHANS), Bengaluru has been found acceptable and feasible for psychiatric patients 53 .…”
Section: Introductionmentioning
confidence: 88%
“…Yoga-add on therapy (YAT: Standard treatment + yoga) : Based on our previous clinical experience the duration of intervention was decided to be 24 weeks 48 – 51 . Yoga will be offered as an add-on to standard treatment.…”
Section: Plan For Researchmentioning
confidence: 99%